Coding of luminance and color differences on neurons in the rabbit’s visual system - Evtikhin, Dmitry V.; Polianskii, Vladimir B.; Alymkulov, Dzekshen E.; Sokolov, Evgenii N. (The Spanish Journal of Psychology, 2008)
The neuronal activity in the rabbit’s visual cortex, lateral geniculate nucleus and superior colliculus was investigated in responses to 8 color stimuli changes in pairs. This activity consisted of phasic responses (50-90 and 130-300 Ms after stimuli changes) and tonic response (after 300 Ms). The phasic responses used as a basis for the matrices (8 8) constructed for each neuron included the average of spikes/sec in responses to all stimuli changes. All matrices were treated by factor analysis and the basic axes of sensory spaces were revealed. Sensory spaces reconstructed from neuronal spike discharges had a twodimensional (with brightness and darkness axes) or four-dimensional (with two color and two achromatic axes) structure. Thus it allowed us to split neurons into groups measuring only brightness differences and the measuring of color and brightness differences between stimuli. The tonic component of most of the neurons in the lateral geniculate nucleus showed linear correlation with changes in intensities; therefore, these neurons could be characterized as pre-detectors for cortical selective detectors. The neuronal spaces demonstrated a coincidence with spaces revealed by other methods. This fact may reflect the general principle of vector coding (Sokolov, 2000) of sensory information in the visual system